2008
DOI: 10.1111/j.1365-2133.2008.08546.x
|View full text |Cite
|
Sign up to set email alerts
|

Rapidly involuting congenital haemangioma associated with transient thrombocytopenia and coagulopathy: a case series

Abstract: Rapidly involuting congenital haemangioma (RICH) may present with thrombocytopenia, low fibrinogen and elevated fibrin degradation products and D-dimers. Such complications have rarely been reported. We wished to define the clinical characteristics of the thrombocytopenia and coagulopathy associated with RICH, to emphasize the transient nature of this haematological complication and to distinguish these abnormalities from true Kasabach-Merritt phenomenon (KMP). We present a case series of seven patients with l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
64
0
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(68 citation statements)
references
References 23 publications
1
64
0
3
Order By: Relevance
“…The thrombocytopaenia in RICH may be a feature of larger lesions as it has never been reported in RICHs of smaller size 18. This consumptive coagulopathy is distinct from the Kasabach-Merritt syndrome, which is associated with profound thrombocytopaenia,19 fibrinogen consumption and secondary formation of D-dimer 20.…”
Section: Discussionmentioning
confidence: 83%
“…The thrombocytopaenia in RICH may be a feature of larger lesions as it has never been reported in RICHs of smaller size 18. This consumptive coagulopathy is distinct from the Kasabach-Merritt syndrome, which is associated with profound thrombocytopaenia,19 fibrinogen consumption and secondary formation of D-dimer 20.…”
Section: Discussionmentioning
confidence: 83%
“…4 RICHs, in some cases, have been associated with thrombocytopenia but with milder and more transient coagulopathy than that seen in Kasabach-Merritt phenomenon (KMP; see discussion that follows); rarely, they can be associated with congestive heart failure. 5,6 Some RICHs show incomplete involution, and it is possible that RICH and NICH lie at opposite ends of the same clinical spectrum. 7,8 Both subtypes of congenital hemangioma were initially believed to be variants of IH that exhibited prenatal growth until North et al 9 showed that, unlike IH, neither lesion expresses glucose transporter protein isoform 1 (GLUT1).…”
mentioning
confidence: 99%
“…This could be because these tumors grow extremely rapidly during the later stages of pregnancy. Although very large CHs may be complicated by cardiac failure, thrombocytopenia, or coagulopathy, 13 these lesions are usually benign, and no treatment is recommended. Ulceration is a common, predominantly benign complication in IH and bleeding seems to occur only rarely and most often is moderate.…”
Section: Discussionmentioning
confidence: 98%